ANALYSIS OF COORDINATION OF OVER CURRENT RELAY (OCR) AND GROUND FAULT RELAY (GFR) ON 20KV DISTRIBUTION SYSTEM CASE STUDY AT PT. PLN (Persero) ULP SIDAREJA: Array - Andriyan, Riki; Nasrulloh; Adzin Murdiantoro, Randi (Program Studi Teknik Elektro Universitas Peradaban, 2022)
Increasing consumers of electrical energy impacts increasing the risk of disruption that distribution systems can expose to consumers. In order not to interfere with the distribution of electrical energy, the protection system installed in the electrical energy distribution network must work optimally. Coordination between protections installed in the distribution network has a significant impact on the quality of distribution. Therefore, the protection components, that is, the reclosing switch, the overcurrent relay (OCR), and the ground fault relay (GFR) must be configured correctly. Proper adjustment is where the protection system works according to its capacity, so the effects of disturbances can be minimized, the disturbances are not widespread and can lead to power outages. The grid protection system from the Lomanis –05 feeder line to ULPSidareja is already good because the components of the protection system are well matched. Since the components do not comply with SPLN 64: 1985 and IEC 60255, that is, 0.35 to 0.4 seconds, we can conclude that the quality of coordination between protection systems is good, but we still evaluate the applied settings. is needed. Not compliant with SPLN 64: 1985, but compliant with IEC60255.